Semantic conflicts detection of heterogeneous messages of Web services: challenges and solution - Al-Baltah, Ibrahim Ahmed; Abdul Ghani, Abdul Azim; Wan Ab. Rahman, Wan Nurhayati; Atan, Rodziah (Science Publications, 2014)
Service Oriented Architecture (SOA) is a new design style that has promised to alleviate the semantic interoperability problem between Web services. Exchanging the messages seamlessly between heterogeneous Web services is required but, it is still difficult due to data heterogeneity. As a result, a noticeable number of works has been proposed with the aim of solving this problem, but yet, the problem has not been solved efficiently. Furthermore, it is important to observe the lack of sufficient approaches in the state of the art, whose purposes are semantic conflicts detection between heterogeneous messages of Web services. It is for these reasons we take a step back to the detection step before providing the solution. This study proposes a new ontology-based approach that aim at detecting semantic conflicts between heterogeneous messages of Web services. The main purposes of this approach are to detect any conflict types between the messages during message exchange process and to identify the conflict type for each detected conflict. The proposed approach plays as a vital step for improving the semantic interoperability between heterogeneous Web service messages, since it facilitate the process of addressing semantic conflicts. A real scenario was used in order to demonstrate the feasibility of the proposed approach.